Contribución al estudio de la flora micológica del Desert de les Palmes (Castelló) - Torrejón Herrero, Miguel (Revista Catalana de Micologia, 2007)
Contribution to the study of fongi in the Les Palmes Desert of Castelló, E-Spain. The author reports in this first contribution 95 species, 2 forms, and 5 varieties of fungi from the Desert deLes Palmes, Castelló, Spain: 2 Myxomycetes, 3 Mitosporic fungi, 14 Ascomycetes, 2 Teliomycetes and82 Basidiomycetes. The samples were collected from 30-10-2000 to 28-7-2001.